The Social Economic Aspect in Selecting Priority Commodities in Community Forest Activities at Protected Forest Areas - Agus Irwanto Wibowo; Yoyok Hendarso; Dessy Adriani (Sriwijaya Journal of Environment, 2021)
The implementation of Community Forestry (CF) in protected forest area is not only intended to improve welfare of community living around forest but also restores the function of protected areas. This study aims to figure out the types of priority crops that can be developed in CF area based on legal aspect of the rules in protected forest areas and social economic aspect of community surround forest areas. The research was conducted for 4 months, on February – May 2020 in working areas of Meranti Wana Makmur Forest Farmers Group (Gapoktanhut), Lubuk Bintialo Village, Batanghari Leko District, Musi Banyuasin Regency. The result showed that according to provisions of utilization in protected forest areas, the types of crops which developed in the CF area, were multipurpose crops and based on social aspects 5 (five) types of crops that had grown and produced were Rubber, Jackfruit, Djenkol bean, Petai bean, and Durian was in “Fairly Priority” category. Therefore, based on the economic aspect, there were only 4 (four) multipurpose plant types of “profitable” categories, such as Jackfruit, Djenkol bean, Petai bean, and Durian. The type of short-term crops function as companion crops (intercrops) that was  good for cultivation were Corn, Chili, Watermelon, and Melon.